Building Critical Awareness of Accounting Students: A Transformative Learning Process - Wahyuni, Andi Sri; Chariri, Anis (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study is intended to describe and critically analysis how transformative learning experienced by accounting students make them more aware on the importance of understanding accounting from social context. As other qualitative research this study, this study was naturally conducted in social setting by using accounting students taking Intermediate Accounting course as informants. All data were based on textual materials generated from the course and its syllabus, fieldnotes and the result of examination. All data were then analyzed critically to obtain the evidence of how transformative learning change students’ paradigm in seeing accounting issues. Our findings show that the implementation of transformative learning have able to change the students’ paradigm and help them solve social problems in their community. This implies that accounting education is not only concerned with conceptual aspects but also concerned with the contextual contents that are rooted in their communities. In other words, when we learn accounting issues in our community, we socially construct our own reality.